Penerapan Kebijakan Intensifikasi dan Ekstensifikasi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) Sebagai Upaya Peningkatan Penerimaan Pajak Daerah Kabupaten Bengkalis - Novira Sartika; Karina Krisnanda (Politeknik Negeri Bengkalis, 2020)
This study aims to determine the application of the intensification and extensification of local tax policies, especially Land and Building Tax in Rural and Urban Areas (PBB-P2) as an effort to increase local tax revenue in Bengkalis Regency and to determine the obstacles in implementing the tax policies. This research is a qualitative research with a qualitative descriptive approach through an interview process with the goverment and several taxpayers. The conclusions of the study are the intensification policy of PBB-P2 has generally been implemented well which is marked by the provision of counseling PBB-P2 both directly and indirectly, administration of the levies and operations of the PBB-P2 have been running well, supervision and control of the levies PBB-P2 has been carried out to all districts, participation in education and training programs related to the management of PBB-P2 is routinely carried out. In other hand, the extensification olicy of PBB-P2 have not been implemented very well. In fact that there are many new objects and subjects of PBB-P2 not registered yet. In addition, investment policies and cooperation with private companies and regional companies have not been made to create new business areas as a new tax objects and new tax subjects. There are several obstacles in implementing the intensification and extensification policy of PBB-P2 in Bengkalis Regency such as limited number of PBB-P2 managers in Bapenda Bengkalis Regency, coordination with regional apparat that manages licenses has not gone well, coordination with goverment of the villages has not gone well, a mobile car for payment of PBB-P2 has been damaged, and also a low awareness of public for the sanctions that have been given.